If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3*x-(6*x)+7*x-14 = x^2+3*x-12+4;x
x
-1/x
3*x-(6*x)+7*x-14 = x^2+3*x-12+4;x
x
abs(x+1) = x+1;x
x
abs(x+2) = 1;x
x
| z(t)=120(1/2)^2000/32760 | | 10+x=11xn | | 21=26-6(-2-2w) | | 14=1/3*b*3 | | q+5-2q-3=4 | | -8w^4(-4+4w+75w^2+3w-13)= | | 9[7-(-6x-9)]=108x+225 | | 3w+2=2w-1 | | 5(y-4)=-22 | | 30*(70-X)/2 | | (2x+4)(2x+5)=306 | | (30(70-X))/2 | | -4x-13x+8=-15x-34 | | (2x+13)=41 | | 9[7-(-6x-9)]=108x+22 | | 9[7-(6x-9)]=108x+225 | | 8=8x-34 | | 32+69+79= | | 5x+13=3(x+4)+2x+1 | | x+32+(x+10)=180 | | 15x+5=8x+12 | | -10x+12=8x-18 | | 4(2x-5)=4x+34+2(2x+3) | | 12=18x-18 | | -2(13x-1)+9(3x-4)-9=5-2 | | 5(x+3)-1=3(x+6) | | 35=9/5y | | 35=5/9y | | 4x+3x-2x=9 | | 3(2x+5)=6-3x | | 5/9(4-32)=-62.F | | 12x-(2x-12)=7+9x |